The Entry of Women as Organic Professionals of Justice Systems: Reflections on Historical Records and Current Trends - Vittorio Olgiati (e-cadernos ces)
In the last decades a rising number of sociolegal studies have been devoted to the official entry of women into Courts of Justice as lawyers, judges and public attorneys. These studies undoubtedly provided significant cognitive hints. It is apparent, however, that the matter still requires a wider perspective and a deeper introspection in order to enlighten the inner rationale, as well as the current social and legal impact, of the entry of women into such a traditional, age-old male-dominated, province of law. Accordingly, most significant historical trends will be outlined to mark basic events that fostered the enrolment of women into Advocacy and Magistracy professional guilds, their active role in Law Courts, and the ongoing collateral effects that such an entry implies, and will imply, as regards the traditional image of Justice systems as a whole.